Clinical and Radiologic Analysis of Posterior Apophyseal Ring Separation Associated with Lumbar Disc Herniation - Bae, Jung-Sik (The Korean Neurosurgical Society, 2013)
OBJECTIVE: We analyzed the clinical and radiologic features of posterior apophyseal ring separation (PARS) with lumbar disc herniation and suggest the proper management options according to the PARS characteristics. METHODS: We reviewed case series of patients with PARS who underwent surgery of lumbar disc herniation. Preoperative symptoms, neurologic status, Body Mass Index, preoperative and postoperative Visual Analogue Scale (VAS) and Korean-Oswestry Disability Index (K-ODI) scores, operation types were obtained. PARS size, locations, the degree of resection were assessed. RESULTS: PARS was diagnosed in 109 (7.5%) patients among 1448 patients given surgical treatment for single level lumbar disc herniation. There were 55 (50.5%) small PARS and 54 (49.5%) large PARS. Among the large PARS group, 15 (27.8%) had lower endplate PARS of upper vertebra at the level of disc herniation. Thirty-nine (72.2%) were upper endplate PARS of lower vertebra. Among the group with upper endplate PARS of lower vertebra, unresected PARS was diagnosed in 12 (30.8%) cases and resected PARS was diagnosed in 27 (69.2%) cases. VAS and K-ODI scores changes were 3.6±2.9 and 5.4±6.4 in the unresected PARS group, 5.8±2.1 and 11.3±7.1 in the resected PARS group. The group with upper endplate PARS of lower vertebra showed significant difference of VAS (p=0.01) and K-ODI (p=0.013) score changes between unresected and resected PARS groups. CONCLUSION: The large PARS of upper endplate in lower vertebra should be removed during the surgery of lumbar disc herniation. High level or bilateral side of PARS should be widely decompressed and arthrodesis procedures are necessary if there is a possibility of secondary instability.